Groundwater recharge in basement aquifers in subhumid drylands of sub-Saharan Africa - D. Mudimbu; W. Namaona; M. C. Sinda; B. Brauns; D. C. Gooddy; W. G. Darling; K. Banda; E. Phiri; P. C. Nalivata; F. Mtambanengwe; P. Mapfumo; A. M. MacDonald; et al. (Hydrogeology Journal, 2024)
Characterising groundwater recharge is fundamental for sustainable groundwater management. This study focuses on assessing recharge in drylands using four experimental plots under different land-use practices in crystalline basement aquifers in three southern African countries (Chitedze in Malawi, Kabeleka and Liempe in Zambia, and Domboshawa in Zimbabwe). Several methods, including water-table fluctuation (WTF), chloride mass balance (CMB), water stable isotopes (δ 18 O and δ 2 H) and dissolved gases, were used to quantify annual recharge rates, recharge sources and groundwater residence times. This informed the development of a conceptual model of groundwater recharge in unpumped basement aquifers. Using WTF, across all sites/years, the range of annual median recharge was found to be in the range of 2.8–14.1% rainfall. Recharge was observed for most years across all sites and was controlled by hydrogeological settings, rainfall totals and antecedent conditions, i.e. the groundwater level at the end of the preceding dry season. Based on groundwater level observations and water stable isotope analysis, for sites where there has been extensive use of conservation agriculture (in time and space), there is some evidence of earlier and greater recharge compared to conventional agriculture at paired sites. Additionally, there is evidence of high lateral connectivity in shallow, permeable layers and high local connectivity in the aquifers which facilitate discharge to surface drainage. This leads to a lower proportion of modern recharge at these unpumped sites (typically <10%) compared to other studies using comparable methods in pumped boreholes, which highlights the importance of groundwater capture due to pumping.

Population dynamics of mixed indigenous legume fallows and influence on subsequent maize following mineral P application in smallholder farming systems of Zimbabwe - Tonny P. Tauro; Hatirarami Nezomba; Florence Mtambanengwe; Paul Mapfumo (Nutrient Cycling in Agroecosystems, 2010)

Nitrogen and phosphorus capture and recovery efficiencies, and crop responses to a range of soil fertility management strategies in sub-Saharan Africa - R. Chikowo; M. Corbeels; P. Mapfumo; P. Tittonell; B. Vanlauwe; K. E. Giller (Nutrient Cycling in Agroecosystems, 2010)

Indigenous legumes biomass quality and influence on C and N mineralization under indigenous legume fallow systems - H. Nezomba; T. P. Tauro; F. Mtambanengwe; P. Mapfumo (Symbiosis, 2009)

Germination, field establishment patterns and nitrogen fixation of indigenous legumes on nutrient-depleted soils - T. P. Tauro; H. Nezomba; F. Mtambanengwe; P. Mapfumo (Symbiosis, 2009)

Smallholder farmer management impacts on particulate and labile carbon fractions of granitic sandy soils in Zimbabwe - F. Mtambanengwe; P. Mapfumo (Nutrient Cycling in Agroecosystems, 2008)

Effects of Organic Resource Quality on Soil Profile N Dynamics and Maize Yields on Sandy Soils in Zimbabwe - F. Mtambanengwe; P. Mapfumo (Plant and Soil, 2006)

Organic Matter Management as an Underlying Cause for Soil Fertility Gradients on Smallholder Farms in Zimbabwe - F. Mtambanengwe; P. Mapfumo (Nutrient Cycling in Agroecosystems, 2005)

Woody legume fallow productivity, biological N2-fixation and residual benefits to two successive maize crops in Zimbabwe - R. Chikowo; P. Mapfumo; P. Nyamugafata; K.E. Giller (Plant and Soil, 2004)

Mineral N dynamics, leaching and nitrous oxide losses under maize following two-year improved fallows on a sandy loam soil in Zimbabwe - R. Chikowo; P. Mapfumo; P. Nyamugafata; K.E. Giller (Plant and Soil, 2004)

Nitrate-N dynamics following improved fallows and maize root development in a Zimbabwean sandy clay loam - R. Chikowo; P. Mapfumo; P. Nyamugafata; G. Nyamadzawo; K.E. Giller (Agroforestry Systems, 2003)